Multi-level strategic alignment within a complex organisation - Lawrie, Gavin; Abdullah, Nur Anisah; Bragg, Christopher; Varlet, Guillaume (Emerald Group Publishing Ltd., 2016)
Purpose: This paper aims to assess the utility of an approach to the design of multiple Balanced Scorecards within large/complex organisations, consider the relevance of “emergent strategising” in this kind of strategy implementation and explore project organisation and wider coordination issues that impact this type of work. Design/methodology/approach: A “research-oriented – action research” approach has been adopted, comprising qualitative observations of an ongoing programme within a major organisation in the Middle East. The case is based on feedback obtained from key actors (participants, facilitators) and the analysis of documentation produced by the project. Findings: Over four years, the project engaged directly with over 200 managers from the organisation’s 35 most senior management units. Its purpose was to align the strategic aims of each unit with those of the organisation and introduce a new form of strategic control. The paper shows that consensus-forming and creation of locally relevant strategic agendas can be usefully and successfully embedded in a large-scale strategic control and alignment programme. The paper notes the large resource implications and duration of such programmes, and the challenges of integrating the resulting processes with those already in place. The paper concludes that for the case organisation, the resource investment appears to have generated useful outcomes. Research limitations/implications: The project relates to a continuing programme within the client organisation that was not explicitly established before it started as an action-research activity. This has limited and constrained the quality of the information reported. Originality/value: The scale of the project, the use of design methods that emphasis consensus forming and local relevance provide novel information and insights.